Rheological properties and 3D printability of SBS/CR-modified asphalt binder with C9 petroleum resin for crack filling - Niu, Yanhui; Wang, Xinyu; Burmistrov, Igor; Niu, Dongyu (Frontiers in Materials, 2024)
This study investigates rheological behavior and 3D printability of SBS-, CR-, SBS/CR-modified asphalt binder with C9 petroleum resin (C9PR) for crack filling. Thirteen types of modified asphalt binders with respective C9PR of 0 wt %, 1 wt %, 2 wt %, 3 wt % were prepared and evaluated for their microstructure, physical properties, compatibility, rheological properties, and 3D printability. The results show that SBS, CR, and C9PR influenced significantly on rheological properties and 3D printability of modified asphalt binders. Physical blending and improved storage stability of modified asphalt binders were observed with the addition of C9PR. In addition, the combination of SBS and CR showed enhanced viscoelastic behavior and temperature sensitivity compared to the base asphalt binder due to the increased swelling behavior of SBS and CR in asphalt binders by C9PR. Furthermore, asphalt binder with 3 wt % SBS, 15 wt % CR, and 1 wt % C9PR showed improved viscosity, elasticity, compatibility, high-temperature rutting resistance, and fatigue resistance. Additionally, C9PR expanded 3D printable temperature range of modified asphalt binder, leading to its potential use as an additive in 3D printed asphalt binders.